2021
DOI: 10.1172/jci.insight.150074
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 receptor blockade does not slow β cell loss in new-onset type 1 diabetes

Abstract: Background IL-6 receptor (IL-6R) signaling drives development of T cell populations important to type 1 diabetes pathogenesis. We evaluated whether blockade of IL-6R with monoclonal antibody tocilizumab would slow loss of residual β cell function in newly diagnosed type 1 diabetes patients. Methods We conducted a multicenter, randomized, placebo-controlled, double-blind trial with tocilizumab in new-onset type 1 diabetes. Participants were screened within 100 days of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 51 publications
0
24
1
Order By: Relevance
“…This is in line with data from NOD mouse studies of IL-1 receptor- or IL-1β-deficient NOD mice, where no protection from diabetes development was observed [ 92 , 93 ]. Likewise, blocking IL-6Ra in a recent trial in individuals with newly diagnosed T1D does not appear to provide benefit [ 94 ].…”
Section: B Cells In T1dmentioning
confidence: 99%
“…This is in line with data from NOD mouse studies of IL-1 receptor- or IL-1β-deficient NOD mice, where no protection from diabetes development was observed [ 92 , 93 ]. Likewise, blocking IL-6Ra in a recent trial in individuals with newly diagnosed T1D does not appear to provide benefit [ 94 ].…”
Section: B Cells In T1dmentioning
confidence: 99%
“…To determine the impact of mbIL-6R blockade on IL-6-related T cell phenotypes in vivo , we analyzed data from the EXTEND clinical trial, which investigated the impact of tocilizumab, a monoclonal antibody targeting global IL-6 signaling by blocking both mbIL-6R and soluble IL-6R, on beta cell loss in pediatric patients with new onset T1D ( 29 ). The EXTEND trial reported a lack of clinical efficacy and no significant changes in the frequency of FOXP3 + Treg, IL-17 + Th17, and IL-21 + Tfh cells.…”
Section: Resultsmentioning
confidence: 99%
“…Supplementary Table 1 lists the individual subjects including demographics, genotypes, and assays performed for each subject. In addition, a post-hoc analysis was performed on data generated in the EXTEND Study, a placebo-controlled, double-blinded, randomized clinical trial of adult and pediatric participants with newly diagnosed T1D testing whether tocilizumab would lead to clinical improvements in T1D ( 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…In line with this observation, other anti‐inflammatory strategies have been tested in type 1 diabetes patients at the onset of the disease. Findings from small pilot clinical trials suggest that inhibition of IL‐1, 23 TNF‐α 24 or IL‐6 signals might have a beneficial effect in type 1 diabetes, but the results were only partially confirmed in randomized phase 2 trials 12,25,26 . On the other hand, six immunotherapies mainly targeting the adaptive lymphocyte‐mediated attack of beta cells have been shown to preserve insulin secretion in stage 3 type 1 diabetes (teplizumab, 3 otelixizumab, 4 rituximab, 5 abatacept, 6 low‐dose antithymocyte globulin 7 and alefacept 8 ) and teplizumab have been shown to delay the onset of stage 2 disease 9 .…”
Section: Discussionmentioning
confidence: 99%